Characterizing Symptoms of Cannabis Use Disorder in a Sample of College Students. (October 2020) - Pellegrino, Alexa J.; Duck, Kerry D.; Kriescher, Dylan P. J.; Shrake, Mackenzie E.; Phillips, Michael M.; Lalonde, Trent L.; Phillips, Kristina T.
Since the legalization of marijuana in several U.S. states in 2012, there has been concern about increases in the development of cannabis use disorder (CUD). The current study examined rates of CUD in Colorado college students who reported regular marijuana use and assessed a range of factors associated with CUD symptoms, including coping motives, concentrate/dab use, mental health concerns (depression, anxiety), age of regular marijuana use, and alcohol use. College students were recruited from a mid-sized university and completed a baseline assessment that included a marijuana urine screen. Participants reported a median of five CUD symptoms and 90% met criteria for CUD. After adjusting for covariates, the age of regular marijuana use was negatively associated with the number of CUD symptoms, while the average daily alcohol drinks was positively associated with the number of symptoms. Prevention and intervention efforts at the university level should be increased to reduce negative outcomes associated with problem marijuana use.